PENGELOLAAN DANA DESA BEBAS FRAUD: PENDEKATAN EFEKTIF DI KECAMATAN TIDORE UTARA - Jeandry, Gregorius; Dara, Amin; Zainuddin, Zainuddin (Politeknik Ganesha Medan, 2024)
Fraud occurs in several sectors, including the village sector, such as fraud in the management of village funds. Village funds that were initially to improve independent villages were not appropriately managed; the management of village funds is synonymous with abuse in management; this is evidenced by the statement